EFFECT OF NUTRITION EDUCATION ON MOTHER’S PRACTICES OF PRE-SCHOOLERS’ NUTRITIONAL NEEDS IN PLATEAU STATE - Bosah, I. P; Hemba, Grace (Journal of Early Childhood and Primary Education, 2025)
This study examined the effect of nutrition education on mothers’ practice of pre-schoolers’ nutritional needs in Plateau State. Two research questions guided the study while two null hypotheses were formulated. The design of the study was quasi-experimental design. The population of this study comprised all the 429 women of child bearing age registered with the five primary health care centres in Pankshin Local Government Area of Plateau State. The sample of this study consisted of 103 women of child bearing age registered from two registered primary health care centres. This selection was made using the multi-stage sampling technique. The instrument used for data collection is an achievement test and questionnaire titled “Test of Mothers’ Knowledge of Preschoolers’ Nutritional Needs” (TMKPNN) and “Questionnaire on Mothers’ Practices of Preschoolers’ Nutritional Needs” (QMPPNN). The instrument was validated by three experts and subjected to test of reliability using Kudar Richardson formula (KR-20) and Cronbach Alpha method settle the coefficient values. Mean and standard deviation scores was used to answer the research questions while ANCOVA was used to test the null hypotheses at 0.05 alpha level. The finding revealed that the mean knowledge scores of mothers exposed to nutrition education is higher than mothers who were not exposed. It was also found that the mean Practice scores of mothers exposed to nutrition education is higher than mothers who were not exposed. It was recommended amongst others that nutrition education should be a core component of pre-natal and post-natal care services. By reaching mothers during critical periods of pregnancy and early child development, these programs can help foster healthier attitudes and knowledge.